A creative primary curriculum for all - Palastanga, Emma L. (Routledge, 2022)
"In many primary schools, in recent history, the curriculum became concerningly narrowed so that children are were being prepared for tests more than their lives were being enriched with a variety of knowledge, skills and experiences that enable them to perform well in tests and in life in general. The time for change is now! This book seeks to empower teachers and school leaders to better understand what is meant by 'curriculum' and what a creative educational diet might look like in each individual school. It explores curriculum intent, implementation, and impact, and includes leaders' reflection boxes and practical suggestions for busy teachers. Sharing examples of lessons and a range of different approaches, Emma Palastanga analyses the need for a broad and balanced curriculum against the limitations of cramming for success and delves deep into the process of curriculum planning, delivery and evaluation using Ofsted's terminology. A Creative Primary Curriculum for All will give all subject leaders, classroom teachers and teacher trainees the confidence to provide a rich, exciting and varied curriculum, meeting the needs of learners but also allowing the craft of teaching and individual inspiration to shine through"--